2018
DOI: 10.1016/j.micres.2017.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Klebsiella sp. confers enhanced tolerance to salinity and plant growth promotion in oat seedlings (Avena sativa)

Abstract: Plant growth and yield is adversely affected by soil salinity. Salt tolerant plant growth-promoting rhizobacteria (PGPR) strain IG 3 was isolated from rhizosphere of wheat plants. The isolate IG 3 was able to grow in presence of NaCl ranging from 0 to 20% in Luria Bertani medium. The present study was planned to evaluate the role of inoculation of PGPR strain IG 3 and its efficacy in augmenting salt tolerance in oat (Avena sativa) under NaCl stress (100mM). The physiological parameter such as shoot length, roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
79
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 197 publications
(89 citation statements)
references
References 47 publications
9
79
0
1
Order By: Relevance
“…However, biofertilization with SCCPVE07 enhances chlorophyll concentration even under saline conditions. Other studies have also reported a significant increased production of photosynthetic pigments in horticultural inoculated plants under salt stress …”
Section: Discussionmentioning
confidence: 81%
“…However, biofertilization with SCCPVE07 enhances chlorophyll concentration even under saline conditions. Other studies have also reported a significant increased production of photosynthetic pigments in horticultural inoculated plants under salt stress …”
Section: Discussionmentioning
confidence: 81%
“…; Singh and Jha ; Sapre et al . ). An important factor to be considered when looking for new isolates is to screen them from environmental conditions for which they would be used (Príncipe et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Sapre et al . ). The great reduction reported in the chlorophyll content in control plants under the salt stress is in line with previous studies (Mahmood et al .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations